The effects of supplementation frequency and amount of urea in dry supplements on intake and digestibility of low-quality tallgrass-prairie forage by beef steers - B.C. Woods; R.C. Cochran; C.P. Mathis; J.S. Heldt; Gerald L. Stokka; K. C. Olson; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 1997)
Sixteen ruminally fistulated steers were used to evaluate the effects of altering supplementation frequency and including urea in dry supplements on forage intake and digestion. Intake of low-quality tallgrass-prairie hay was not affected by supplementation frequency or by the inclusion of urea. Supplementing cattle less frequently resulted in a decrease in diet digestion. However, we observed a slight trend for reduced supplementation frequency to exert a greater impact when cattle were fed supplements that contained urea.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Steers; Forage; Urea; Supplementation frequency; Intake; Digestibility